Synthesis of Cordyceps fumosorosea-Biochar Nanoparticles and Their Effects on Growth and Survival of Bemisia tabaci (Gennadius) - Wang, Xingmin; Xu, Jing; Sun, Tingfei; Ali, Shaukat (Frontiers in Microbiology, 2021)
Nanotechnology can offer an environmentally sustainable alternative to synthetic chemicals for pest management. Nano-formulations of different microbial pest control agents have been effective against several insect pests. Synthesis of Cordyceps fumosorosea-biochar (BC) nanoparticles and their bio-efficacy against Bemisia tabaci was observed during this study. The characterization of C. fumosorosea-BC nanoparticles through different analytical techniques showed successful synthesis of nanoparticles. UV spectroscopy showed a characteristic band of surface plasmon between 350-400nm; SEM images confirmed the synthesis of spherical shaped nanoparticles; X-ray diffractogram showed strong peaks between 2θ values of 20-25°; and atomic force microscopy (AFM) analysis revealed particle size of 49.151 nm. The bioassay studies demonstrated that different concentrations of C. fumosorosea-BC nanoparticles caused significant reduction in hatchability of B. tabaci eggs as well as survival of immatures emerging from treated eggs when compared with controls. The results also revealed that C. fumosorosea-BC nanoparticles were highly pathogenic against 2nd and 3rd instar nymphs and pupae of B. tabaci having LC50 values of 6.80, 7.45 and 8.64 ppm, respectively. The LT50 values for 20 ppm concentration of C. fumosorosea-BC nanoparticles against 2nd and 3rd instar nymphs, and pupae of B. tabaci were 3.25 ± 0.29, 3.69 ± 0.52 and 4.07± 0.51 days, respectively. These findings suggest that C. fumosorosea-BC nanoparticles can potentially be used in biorational B. tabaci management programs.